Catalysing Environmental Action: a Governance Framework for Enhancing Individual Participation in Sub-Saharan Africa's Plastic Circular Economy. - Ambituuni, Ambisisi; Ajala, Olubunmi; Schroeder, Patrick; Oyinlola, Muyiwa (Environmental Management, 2025)
Plastic waste poses a significant challenge to achieving sustainable production and consumption of resources, particularly in sub-Saharan Africa where effective governance and waste management systems are lacking. In this paper, we develop an empirical understanding of the influence of public governance system on promoting circular economy (CE) for plastic actions among individuals. Through a survey of 1475 participants across five sub-Saharan African countries, we tested five hypotheses drawing on New Governance Theory and CE Action Recipe to explore the relationship between governance and individual's actions supporting CE for plastic. We found that a governance system that supports CE practices and exhibits governance efficiency is positively associated with individuals' actions supporting CE for plastic. The awareness of government policies, laws and regulations, institutions, processes, and programmes have a significant impact on individuals' engagement in plastic circularity practices. The paper's theoretical and governance implications highlight the relevance of public governance in shaping action towards a CE for plastic at the individual level.